Implantable Biosensors for Vascular Diseases: Directions for the Next Generation of Active Diagnostic and Therapeutic Medical Device Technologies - Ali Mana Alyami; Mahmut Talha Kirimi; Steven L. Neale; John R. Mercer (Biosensors)
Cardiovascular disease remains the leading cause of morbidity and mortality worldwide. Key challenges such as atherosclerosis, in-stent restenosis, and maintaining arteriovenous access, pose urgent problems for effective treatments for both coronary artery disease and chronic kidney disease. The next generation of active implantables will offer innovative solutions and research opportunities to reduce the economic and human cost of disease. Current treatments rely on vascular stents or synthetic implantable grafts to treat vessels when they block such as through in-stent restenosis and haemodialysis graft failure. This is often driven by vascular cell overgrowth termed neointimal hyperplasia, often in response to inflammation and injury. The integration of biosensors into existing approved implants will bring a revolution in cardiovascular devices and into a promising new era. Biosensors that allow real-time vascular monitoring will provide early detection and warning of pathological cell growth. This will enable proactive wireless treatment outside of the traditional hospital settings. Ongoing research focuses on the development of self-reporting smart cardiovascular devices, which have shown promising results using a combination of virtual in silico modelling, bench testing, and preclinical in vivo testing. This innovative approach holds the key to a new generation of wireless data solutions and wireless powered implants to enhance patient outcomes and alleviate the burden on global healthcare budgets.